EFFECT OF PROFESSION ON CONSUMPTION OF POTATO PRODUCTS IN GREATER KOLKATA AND NEARBY AREAS - K. Rana, Rajesh; Pandey, N K.; Pandit, Arun; Kumar, N. R. (Potato Journal, 2013)
Monthly family expenditure on potato chips, alu bhujia and French fries over three points in time, viz., current, five years back and expected in next five years. Consumption expenditure on potato processed products under organized and unorganized sectors was studied separately. Potato products from organized sector were more popular with the service class while farmers and labour class preferred potato products from unorganized sector. Consumption growth for potato chips was expected to be lower than that experienced in past, while French fries were expected to observe phenomenal growth of 74% over coming five years.